2007
DOI: 10.1103/physrevb.75.195201
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast dynamics of singlet-singlet and singlet-triplet exciton annihilation in poly(3-2-methoxy-5octylphenyl)thiophene films

Abstract: Singlet-singlet ͑S-S͒ and singlet-triplet ͑S-T͒ exciton annihilation was studied in poly͑3-2Ј-methoxy5Јoctylphenyl͒thiophene films. For the S-S exciton annihilation studies, transient absorption spectroscopy at excitation laser pulse fluences of 1.2ϫ 10 13 -4.4ϫ 10 14 photons/ cm 2 and 2.5 kHz pulse repetition rate was applied. The obtained kinetics demonstrate a typical nonexponential character with intensity-dependent amplitudes and lifetimes. In time-resolved fluorescence experiments, low excitation pulse f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 33 publications
4
46
0
Order By: Relevance
“…To give an idea of the precision of the fit, we include dotted lines that correspond to annihilation constants of 6 × 10 -8 (below) and 1.5 × 10 -8 cm 3 s -1 (above), respectively, roughly double or half the best fit value. This value of ∼3 × 10 -8 cm 3 s -1 for the annihilation constant is, therefore, a reasonable precise value and is furthermore comparable to thatreportedforotherconjugatedpolymersintheliterature, 31,39,41,42,[50][51][52][53][54][55] where annihilation constants on the order of 10 -8 cm 3 s -1 are typical.…”
Section: Resultssupporting
confidence: 63%
“…To give an idea of the precision of the fit, we include dotted lines that correspond to annihilation constants of 6 × 10 -8 (below) and 1.5 × 10 -8 cm 3 s -1 (above), respectively, roughly double or half the best fit value. This value of ∼3 × 10 -8 cm 3 s -1 for the annihilation constant is, therefore, a reasonable precise value and is furthermore comparable to thatreportedforotherconjugatedpolymersintheliterature, 31,39,41,42,[50][51][52][53][54][55] where annihilation constants on the order of 10 -8 cm 3 s -1 are typical.…”
Section: Resultssupporting
confidence: 63%
“…the density of quenching sites is virtually constant as well, the fluorescence dynamics prevail a mono-exponential decay but the obtained kinetics may not represent the truly intrinsic fluorescence lifetimes anymore. It should be noted that the results of Zaushitsyn et al [45] are in contrast to the observations of King et al who have reported the absence of singlet-triplet annihilation in a prototypical polyfluorene. [37] Singlet Energy Transfer in Blends of Conjugated Polymers…”
mentioning
confidence: 65%
“…Recently, earlier results on the origin of DF in MeLPPP have been revisited and it has been proposed that TTA is the only origin of DF in MeLPPP. [44] In bulk samples triplet states can accumulate under continuous wave (cw) or quasi-cw excitation at high laser repetition rates as recently demonstrated by Zaushitsyn et al [45] This opens additional quenching channels for singlet states, if singlet-triplet annihilation is turned on upon excited triplet state accumulation. The effect of singlet-triplet annihilation on the lifetime of the excited singlet state can be quite drastic leading to shortening of the measured fluorescence lifetime with increasing repetition rate of the pump laser.…”
mentioning
confidence: 91%
“…However, although theoretically possible, once again the Förster radius is very small. In the case of S-T annihilation there have been only a few reports of triplets efficiently quenching singlet states in polyfluorene, either in the solid state and in single molecule studies and the efficiency of the observed process is much lower than singletsinglet annihilation [85,86]. The efficiency of S-S annihilation is enhanced by the migration of the singlets, but the migration does not seem to dramatically enhance the efficiency of S-T annihilation.…”
Section: Singlet-triplet Annihilationmentioning
confidence: 94%